FUNCTIONAL DELAYED ECHOLALIA: INSIGHTS FROM A MOVIE - Qonitah Nuri Humaira; Emy Sudarwati (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study focuses on the analysis of functional delayed echolalia towards an autistic individual in   Life, Animated documentary. The obtained data were derived from Owen Suskind's utterances and words in the aforementioned documentary, which the researchers manipulated and structured to fall into two categories of functional delayed echolalia. The study used qualitative descriptive method in analyzing the functional delayed echolalia of Owen Suskind using interactive and non-interactive functional categories of delayed echolalia theory proposed by Vicker (1999). The findings show that there are 8 (eight) out of 9 (nine) types of interactive delayed echolalia were discovered namely   Turn taking, Verbal, Completion,   Providing information, Labelling,   Protest,   Request,   Calling and Affirmation. Meanwhile, the non- interactive   delayed echolalia consists of three types namely   non-focused,   situation association, and   rehearsal.   The findings of this study are expected to give   a positive impact on both readers who are dealing with children with autism who have echolalia. It will provide information on their language development in order to later determine the ideal method to handle them with care.